Bushen huoxue decoction inhibits RANKL-stimulated osteoclastogenesis and glucocorticoid-induced bone loss by modulating the NF-κB, ERK, and JNK signaling pathways - Liu, Yamei; Fu, Binlan; Li, Xiaoman; Chen, Chen; Li, Xican; Xu, Liangliang; Wang, Bin (Frontiers in Pharmacology, 2022)
Glucocorticoid-induced osteoporosis (GIOP) is the most common form of secondary osteoporosis, which is caused by a disorder in bone metabolism due to excessive activation of osteoclasts. Bushen Huoxue decoction (BHD) is an herbal formula with multiple pharmacological effects, including anti-inflammatory, antioxidant activity and stem cell migration promotion. However, the effect of BHD on osteoclastogenesis has not been reported. In this study, we aimed to elucidate the effect of BHD on RANKL-stimulated osteoclastogenesis and explored its underlying mechanisms of action in vitro. Our results show that BHD had no effect on BMMs and RAW264.7 cells viability, but inhibited RANKL-induced osteoclast formation in vitro. Furthermore, BHD attenuated RANKL-induced NF-κB, ERK, and JNK signaling. The attenuation of NF-κB, ERK, and JNK activation were enough to impede downstream expression of c-fos and NFATc1 and related specific genes. Meanwhile, we investigated the therapeutic effect of BHD on glucocorticoid-induced osteoporosis (GIOP) mice. The result indicated that BHD prevents glucocorticoid-induced osteoporosis and preserves bone volume by repressing osteoclast activity. Collectively, BHD shows significant osteoclast inhibition and holds great promise in the treatment of osteoporosis.